Immune-mediated hepatitis induced by immune checkpoint inhibitors: Current updates and future perspectives - Liu, Zherui; Zhu, Yun; Xie, Huan; Zou, Zhengsheng (Frontiers in Pharmacology, 2023)
In recent years, cancer immunotherapy has made remarkable achievements. Immune checkpoint inhibitors (ICIs) have been used successfully in several types of cancer in the past decade. However, expanded indication and increased use of ICIs have resulted in increased reports of toxicity called immune-related adverse events (irAEs). Due to the unique immunological characteristics of the liver, a hepatic irAE has also been reported, which is usually termed immune-mediate hepatitis (IMH). So far, it is generally considered that the mechanism of IMH induced by ICIs is mainly the overactivation of T cells. It has been reported that the incidence of IMH ranges from 1% to 15%. Because of the lack of specific markers, a diagnosis of exclusion of IMH is critical. Although most IMH is mild and recoverable, several death cases have been reported, which has been increasingly concerned. This review summarizes the current understanding of the pathophysiology, epidemiology, diagnosis, management and prognosis of IMH caused by ICIs. It also discusses the controversial issues in IMH, such as the role of liver biopsy, grading criteria, risk factors, rational treatment strategies with steroids, and the timing of ICIs rechallenging, which may provide helpful information for IMH in future clinical practice.